Imaging in the diagnosis of idiopathic inflammatory myopathies; indications and utility. (1st February 2019) - Paramalingam, Shereen; Counsel, Peter; Mastaglia, Frank L.; Keen, Helen; Needham, Merrilee
ABSTRACT: Introduction : Idiopathic inflammatory myopathies (IIM) are a heterogeneous group of muscle diseases that carry a significant morbidity and mortality risk. The utilization of imaging in the diagnostic pathway of IIM is therefore important to obtain early diagnosis and even monitor patients over time. Areas covered : Magnetic resonance imaging (MRI) has been the main imaging modality used to detect myositis but limitations include cost and accessibility, leading to delays in time to scan, and patient contraindications. This has led to the exploration of other imaging techniques to diagnose and monitor response to therapy. This article is based primarily on a literature search via PubMed using Boolean terms 'myositis' and the various imaging modalities. Expert opinion : Imaging is sensitive to pathology in IIM and may contribute to the diagnostic process. Learning how specific imaging features can distinguish different forms of IIM may allow more rapid diagnosis of myositis subtype and treatment planning, and to monitor disease activity particularly in patients who respond poorly to treatment. However, more work is needed to investigate the validity and relative utility of these imaging modalities.